EVALUASI SISTEM INFORMASI REKAM MEDIS DI RUMAH SAKIT BRAYAT MINULYA - Nurhayati Nurhayati; Sri Widodo; Antonius Suhartanto (Nusantara Hasana Berdikari, 2021)
Motivation/Background: Brayat Minulya Hospital already uses a medical record information system, but no evaluation has been done. Constraints were found including the reports generated by the system were invalid and real time, there was duplication of patient data. This study aims to evaluate the system using the PIECES method. Method: This research was conducted in March-June 2018. This type of research is descriptive with a cross sectional approach. The research variables are performance, information, economy, control, efficiency, service. Data collection techniques are interviews and observation. Processing of data collecting, editing, coding, classification and tabulating. Research instruments include interview guidelines, observation guidelines and questionnaires. Results: The Performance aspect is considered quite good by the registration section, service staff, but not good enough in the reporting section. The information aspect produced by the system is not good in all units because it does not meet the needs of hospital statistical data. The economy aspect of the system is considered poor because the resulting data still has to be crosschecked. The control aspect of the system is considered very good because it meets the data security aspect. The efficiency aspect of the system is good enough to increase time efficiency, but in the reporting section it is not good. The service aspect of the system for accuracy and speed is still quite good, the system is easy to learn. Conclusions: The medical record information system is good in terms of performance and data security but is lacking in terms of the accuracy of the information and reports generated.